Definition of certified values of normalized metrological characteristics of the reference material of chernozem ordinary - Prokhorova І.А. (AgroChemistry and Soil Science, 2016)
Reference materials of soil is a prerequisite for effective measurement of agrochemical laboratories during the analysis of soil samples. Interlaboratory validation reference material - appraisal method based on the use of measurement results that are independently perform several laboratories, using one or more methods. This procedure is designed to reliably describe the uncertainty of set values of certified reference materials. Objective: to establish the value of normalized metrological characteristics (pH of salt extract, hydrolytic acidity and table of contents of carbon organic matter) and error (or uncertainty) on the results of an interlaboratory validation, evaluating the quality of the results provided by the laboratory for Z-index. Samples for inter-laboratory comparative tests were prepared in the soil instrumental methods laboratory of NSCAR named after O.N. Sokolovsky. Original material for the sample – ordinary light-clay chernozem. During the sample preparation were used procedures of drying, grinding, homogenization. Two hundred fifty grams of soil sample were given to laboratories and was suggested to analyze it with proposed methods in the terms of reiteration for content of pH salt extraction, carbon organic matter, hydrolytic acidity. For data’ statistical treatment was used ANOVA statistics and robust statistics algorithm. Conclusion about the measurement results quality on each component in each sample was done on the basis of values’ comparison. The treatment of the experimental data was carried out taking into account received by all laboratories participating parameters measured soil characteristics. For statistical data used ANOVA statistics and robust statistical algorithm that includes such components to establish a statistical estimation - characteristics of error of the results obtained in the course of inter-laboratory validation and evaluation of the quality measurements using Z-index. A number of experimental data, with a confidence level of 95% approximated by the normal distribution, calculated the valuation of properties (agrochemical parameters) of the material according to DSTU-N ISO Guide 35 "Certification of reference materials. General and statistical principles. " Applying a non-parametric method GOST 8.532. Conclusion about the measurement results quality on each component in each sample was done on the basis of values’ comparison.Value of Z-indexes (calculated on agrochemical indicators such as hydrolytic acidity and available organic matter) for all laboratories-participants of inter-laboratory comparative tests fulfill such conditions | Z | ≤ 2. Unacceptable result was received during estimation of carbon organic matter in analytical laboratory 9. Results of all other participants were appreciated as satisfactory cause their value of Z-indexes, received during estimation of required soil indicator, fulfill such conditions | Z | ≤ Z ' = 2 . According to the results of statistical processing of the data provided by participating laboratories interlaboratory certification, established certified values and error (or uncertainty) certified values pH salt extraction, carbon organic matter, hydrolytic acidity in a material candidate for the creation of a standard sample composition (agrochemical parameters) of ordinary chernozem.